2010
DOI: 10.3233/jad-2010-1208
|View full text |Cite
|
Sign up to set email alerts
|

Is Frontotemporal Lobar Degeneration a Rare Disorder? Evidence from a Preliminary Study in Brescia County, Italy

Abstract: Frontotemporal Lobar Degeneration (FTLD) has always been considered a rare disorder, but only a few epidemiologic studies are available. The aim of the present work was to ascertain all FTLD patients in a Northern Italy area from January 2001 to December 2008, and to estimate the disease prevalence. On the census day, 213 FTD patients were still alive, resulting in an overall prevalence of 17.6 per 100,000 inhabitants. The prevalence of FTLD in patients aged 45-65 years was 22 per 100,000 inhabitants (95% CI=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 14 publications
4
52
0
2
Order By: Relevance
“…Indeed, only a few studies have specifically addressed the epidemiology of FTLD with a wide range of results. Two independent studies in the UK reported a prevalence of 15 per 100,000 inhabitants in subjects aged 45-65 years and one Italian study obtained the prevalence of 17.6 per 100,000 inhabitants in people of all ages [1,2,23]. Conversely, a study from the Netherlands estimated a significantly lower prevalence of 2.7 per 100,000 in the entire population [24].…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, only a few studies have specifically addressed the epidemiology of FTLD with a wide range of results. Two independent studies in the UK reported a prevalence of 15 per 100,000 inhabitants in subjects aged 45-65 years and one Italian study obtained the prevalence of 17.6 per 100,000 inhabitants in people of all ages [1,2,23]. Conversely, a study from the Netherlands estimated a significantly lower prevalence of 2.7 per 100,000 in the entire population [24].…”
Section: Discussionmentioning
confidence: 86%
“…population as a whole FTLD is a rare disorder [1] and classified as an orphan disease (Orpha number ORPHA282 of www.orpha.net). The estimated prevalence is 15-22/100,000 [2].…”
Section: Introductionmentioning
confidence: 99%
“…FTLD is a more common form of dementia than previously recognized, with prevalence of up to 17 cases per 100,000 inhabitants [2]. Despite clear-cut neuroimaging features, affecting frontal and temporal lobes [3], no diagnostic biological markers are available yet.…”
Section: Introductionmentioning
confidence: 99%